Tong-Xie-Yao-Fang Regulates 5-HT Level in Diarrhea Predominant Irritable Bowel Syndrome Through Gut Microbiota Modulation - Li, Junchen; Cui, Huantian; Cai, Yuzi; Lin, Jin; Song, Xin; Zhou, Zijun; Xiong, Wantao; Zhou, Huifang; Bian, Yuhong; Wang, Li (Frontiers in Pharmacology, 2018)
Tong-Xie-Yao-Fang (TXYF) has been widely used for the treatment of diarrhea-predominant irritable bowel syndrome (IBS-D) in traditional Chinese medicine. However, its mechanism of action in the treatment of IBS-D remains to be fully understood. Recent reports have shown that Clostridium species in the gut can induce 5-HT production in the colon, which then contributes to IBS-D. Due to the wide use of TXYF in the clinical treatment of IBS-D and the close relationship between gut microbiota and IBS-D, we hypothesize that TXYF treats IBS-D by modulating gut microbiota and regulating colonic 5-HT levels. In this study, variation analysis of 16S rRNA was conducted to evaluate changes in the distribution of gut microbiota in IBS-D model rats after TXYF treatment. Moreover, we investigated whether TXYF could affect colonic 5-HT levels in IBS-D model rats. We then performed fecal transplantation experiments to confirm the effects of TXYF on gut microbiota and 5-HT levels. We found that TXYF treatment can ameliorate IBS-D and regulate 5-HT levels in colon tissue homogenates. TXYF treatment also affected the diversity of gut microbiota and altered the relative abundance of Akkermansia and Clostridium sensu stricto 1 in gut flora populations. Finally, we showed that fecal transplantation from TXYF-treated rats could relieve IBS-D and regulate 5-HT levels in colon tissue homogenates. In conclusion, the present study demonstrates that TXYF treatment diminishes colonic 5-HT levels and alleviates the symptoms of IBS-D by favorably affecting microbiota levels in gut flora communities.